The Smart Health Medicare System - Murali, A; Raj, A; Aifa, S; Nair, AS; Vincent, C (International Journal of Computer Sciences and Engineering, 2025)
Existing Information System of hospitals mainly focuses on single and separated hospitals. The Smart Health system interconnects multiple hospitals. The project’s aim is to develop a wide range of hospital administration processes. This system helps patients to get their information (medical report, lab report) in every hospital with a user name and password. There is no need to carry all medical copies (medical report & lab report). Patients, lab technicians, doctors and hospitals can make use of this software. Better health is central to human happiness and well-being. It provides progress of economics. The project comprises software for doctors and hospitals and a mobile application running on android for the patients. The patient can get the details of the doctors, appointment times, laboratory tests and the specific medicine about his/her medical situation using the system. It also provides assistance for the doctors to retrieve the previously given prescriptions and results of a patient and directly sends lab requests to lab technicians. The software provides security of data, authentication and avoid duplicate entry of data. The patient can book is/her on-line appointment with a mobile phone application. The system helps to save the time of patients as well as the time of doctors. It also reduces the paper work of receptionists.